'Trafficking' or 'personal use': Do people who regularly inject drugs understand Australian drug trafficking laws?. (15th July 2014) - Hughes, Caitlin E.; Ritter, Alison; Cowdery, Nicholas; Sindicich, Natasha
Abstract Introduction and Aims Legal thresholds for drug trafficking, over which possession of an illicit drug is deemed 'trafficking' as opposed to 'personal use', are employed in all Australian states and territories excepting Queensland. In this paper, we explore the extent to which people who regularly inject drugs understand such laws. Design and Methods Participants from the seven affected states/territories in the 2012 Illicit Drug Reporting System (n = 823) were asked about their legal knowledge of trafficking thresholds: whether, if arrested, quantity possessed would affect legal action taken; and the quantities of heroin, methamphetamine, cocaine and cannabis that would constitute an offence of supply. Data were compared against the actual laws to identify the accuracy of knowledge by drug type and state, and sociodemographics, use and purchasing patterns related to knowledge. Results Most Illicit Drug Reporting System participants (77%) correctly said that quantity possessed would affect charge received. However, only 55.8% nominated any specific quantity that would constitute an offence of supply, and of those 22.6% nominated a wrong quantity, namely a quantity that was larger than the actual quantity for supply (this varied by state and drug). Discussion and Conclusions People who regularly inject drugs have significant gaps in knowledge about Australian legal thresholds for drug trafficking, particularly regarding the actual threshold quantities. This suggests that there may be a need to improve education for this population. Necessity for accurate knowledge would also be lessened by better design of Australian drug trafficking laws. [Hughes CE, Ritter A, Cowdery N, Sindicich N. 'Trafficking' or 'personal use': Do people who regularly inject drugs understand Australian drug trafficking laws? Drug Alcohol Rev 2014;33:658‐666]